2021
DOI: 10.2217/imt-2021-0035
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Immune Checkpoint Inhibitor Therapy in Patients With RET Fusion-Positive Non-Small-Cell Lung Cancer

Abstract: Aim: To describe outcomes of patients with RET fusion-positive non-small-cell lung cancer (NSCLC) who received immune checkpoint inhibitor (ICI)-based treatments in the US. Patients & methods: Using de-identified Flatiron Health-Foundation Medicine NSCLC Clinico-Genomic and Guardant Health databases, treatment patterns and outcomes of 69 patients with advanced/metastatic RET fusion-positive NSCLC who received ICI-based treatment were described. Results: Median real-world progression-free survival and overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…Response to immunotherapy and chemotherapy Like patients with NSCLC harboring ALK or ROS1 rearrangements, RET-rearranged lung cancers can respond to pemetrexed-based doublet chemotherapy with an objective response rate (ORR) of 45% and median progression-free survival (PFS) of 19 months [61]. There is emerging data on the response to immunotherapy in RET-altered cancers [62][63][64]. A study of 74 patients with RET-rearranged lung cancers who were treated with immune checkpoint inhibitors (ICI) either as single-or dual-agent immunotherapy [63] (Table 1) revealed that RET-rearranged lung cancers have low levels of PD-L1 expression and low tumor mutation burden in the majority of patients and poorer responses to immunotherapy.…”
Section: Treating Ret-altered Cancersmentioning
confidence: 99%
“…Response to immunotherapy and chemotherapy Like patients with NSCLC harboring ALK or ROS1 rearrangements, RET-rearranged lung cancers can respond to pemetrexed-based doublet chemotherapy with an objective response rate (ORR) of 45% and median progression-free survival (PFS) of 19 months [61]. There is emerging data on the response to immunotherapy in RET-altered cancers [62][63][64]. A study of 74 patients with RET-rearranged lung cancers who were treated with immune checkpoint inhibitors (ICI) either as single-or dual-agent immunotherapy [63] (Table 1) revealed that RET-rearranged lung cancers have low levels of PD-L1 expression and low tumor mutation burden in the majority of patients and poorer responses to immunotherapy.…”
Section: Treating Ret-altered Cancersmentioning
confidence: 99%
“…Non-small cell lung cancer (NSCLC) accounts for approximately 85% of lung cancer cases, which comprises approximately 40–50% cases of lung adenocarcinoma (LUAD) and 20–30% cases of lung squamous cell carcinoma (LUSC) ( Liu et al, 2021 ; Siegel et al, 2020 ). Despite advances in chemoradiotherapy and targeted therapies, immune checkpoint inhibitors (ICI), including programmed death-ligand 1 (PD-L1), programmed cell death 1 (PD-1), and cytotoxic T lymphocyte antigen-4 (CTLA-4) represent promising advances in the treatment of lung cancer ( Hiley et al, 2016 ; Bhandari et al, 2021 ; Fountzilas et al, 2021 ); however, the clinical response rate of ICIs is only 20%, which can seriously hinder its wider application ( Borghaei et al, 2015 ; Brahmer et al, 2015 ; Reck et al, 2016 ; Rittmeyer et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Low intracranial activity of available treatment methods, including immunotherapy, poses a significant challenge in treatment of patients with RET gene fusion. Bhandari et al have recently published results of analysis using data from Flatiron Health-Foundation Medicine Clinico-Genomic Database and Guardant Health Database [ 22 ]. In total, 264 patients with RET fusion were identified and 69 of them had received immunotherapy as first- or second-line treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 264 patients with RET fusion were identified and 69 of them had received immunotherapy as first- or second-line treatment. Median PFS in patients receiving immunotherapy as first-line treatment was 4.2 months (95%CI 1.4–8.4), while mOS—19.1 months (available data for 17 patients included in Clinico-Genomics Database) [ 22 ]. For 12 patients who received chemoimmunotherapy as first-line treatment mPFS was 5.4 months and mOS—19.1 months (6.9-NR); ORR of 70% was noted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation